Juvenile Criminal Handling in Indonesia: A Review Through Gustav Radbruch’s Legal Purpose Theory - Haris, Alief Abdul; Afiyah, Siti; Hudi, Moh.; Munir, Ahmad (Fakultas Syariah INSURI Ponorogo, 2026)
This study examines the imbalance in the application of justice, legal certainty, and legal expediency in handling juvenile criminal cases in Indonesia. The problem addressed concerns the extent to which regulations and practices in juvenile criminal justice reflect Gustav Radbruch's Legal Purpose Theory. This research aims to analyze the conformity between legal norms and their implementation with the values of justice, legal certainty, and expediency. The study employs a normative legal research method, drawing on statutory and conceptual approaches. Primary legal materials include laws and regulations governing juvenile criminal justice. In contrast, secondary legal materials include books, journal articles, and Supreme Court Annual Reports 2021–2025, particularly statistical data on juvenile criminal cases and diversion practices in Indonesian district courts. The findings demonstrate that, normatively, Indonesia's juvenile justice system has adopted restorative justice through diversion mechanisms, reflecting the values of justice and expediency. However, in practice, there remains an imbalance in implementation, particularly regarding legal certainty and the protection of victims' interests. Statistical data also reveal fluctuations in diversion success rates, suggesting inconsistent implementation across law enforcement institutions. In several cases, the dominance of expediency risks undermining substantive justice. Therefore, strengthening the implementation of juvenile criminal justice is necessary by prioritizing justice while maintaining a proportional balance with legal certainty and expediency.